Metode Role Playing Dalam Pembelajaran Profesi Kependidikan (Studi Kasus Mahasiswa Prodi Pendidikan Bahasa Inggris Universitas Indraprasta PGRI) - Anggraeni, Anastasia Dewi (FKIP Universitas Lampung, 2018)
Role Playing Method in teaching profession learning. This study aims to evaluate the influence of the role playing method on student learning outcomes and activities. This research was conducted on the students of English Education Study Program of Indraprasta PGRI University in the first semester used Classroom Action Research (PTK) method, which was consisted of 65 students.. Data collected techniques used observation and evaluation. The results showed that the role playing method gave a significant influence in the lecturing education proffesion subject. In other words, the student’s learning outcomes and activity were increasing. These results can be seen from each cycle, 72% for the first cycle and 86% for the second cycle.Keywords: role playing, educational profession DOI: http://dx.doi.org/10.23960/jpp.v8.i1.201806